Impact of urbanization on the water quality, fish habitat, and fish community of a Lake Ontario marsh, Frenchman’s Bay - Seilheimer TS; Wei A; Chow-Fraser P; Eyles N (Springer Nature, 2007)
Frenchman's Bay is a barrier beach wetland with a highly urbanized watershed located east of Toronto, along the north shore of Lake Ontario. Degradation of water quality has reduced the historically large stand of emergent vegetation to fringe emergent beds to the north and south of the Bay. Altered hydrology and runoff from the urban watershed and a nearby major highway have resulted in poor water quality, and warmer waters at the northern site. By contrast, the southern site has considerably cleaner and cooler water, as it is influenced by exchange of good-quality water with Lake Ontario. These differences in water quality were reflected in the composition of the fish assemblages that were sampled at the two sites over a 2-year period. Comparisons with past studies indicate that the dominant fish community of Frenchman's Bay has been relatively stable for the last 20 years. Scores for the Wetland Fish Index, an indicator of wetland condition, were significantly higher in the south site than in the north site, which corresponded to significant differences in Water Quality Index scores. Although the northern portion of Frenchman's Bay shows clear signs of degradation, the southern portion contains important fish habitat for western Lake Ontario. © 2007 Springer Science+Business Media, LLC.
Keywords: 31 Biological Sciences; 3103 Ecology